PROSES PENGGUNAAN MEDIA PEMBELAJARAN MONTESSORI PADA MATERI PENJUMLAHAN DAN PENGURANGAN UNTUK SISWA KELAS 1 SD - Yuli Hartati; Moh. Liwa Ilhamdi; Baiq Niswatul Khair (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to determine the process of using the addition and subtraction montessori learning media on the addation and subtraction material for grade 1 elementary school students. This research is a descriptive qualitative study with 21 students as respondents consisting of 11 male and 10 female. Data obtained through the results of questionnaires, interviews, dan observations. Based on the results of the study, it shows that out of 21 students 19 student understand addition and subtraction material and cas use addition and subtraction board learning media very well difficuly understanding addation and subtraction material because these students experience slow learning.